Phase recovery with intensity and polarization correlation - Sarkar T.; Chandra S.; Singh R.K. (My University, 2025)
The challenge of phase recovery from the experimentally available magnitude of the signal appears in various fields of science and engineering. To prepare a broad framework and include the correlations in the phase recovery, we frame this review article in two major portions to cover the phase recovery challenge appearing due to two different reasons. The first part covers conventional optics where phase loss in the experimental measurement is attributed to the high frequency of the light. To overcome this issue, several iterative and non-iterative techniques have been proposed. Among these techniques, a non-iterative holographic interferometric approach has attracted prominent interest in phase recovery. The second part, mainly, is devoted to the phase recovery in the optics with or through random scattering media. A phase loss in the autocorrelation of the random intensity and recovery of the phase from the correlations has a different origin in comparison to the previously mentioned phase recovery challenge. This topic has attracted significant attention in astronomical imaging, unconventional holography, and coherence optics. Despite such challenges and constraints, the use of randomness through correlations of the light offers a new way and direction for innovations in phase recovery methods. A combination of the holography with the Hanbury-Brown Twiss approach in the intensity interferometer offers new and highly stable experimental methods to overcome the phase loss problem in the intensity correlations. Some significant developments in the area of phase recovery using polarization correlation through randomness have been introduced, overcoming the issues of intensity correlation. © 2023 Elsevier B.V.